The influence of faecal egg counts and fungal dose levels on the nematode-trapping capability of Duddingtonia flagrans against free-living stages of gastrointestinal nematodes of cattle - WARUIRU, R M (The Indian Journal of Animal Sciences, 2014)
In an in-vitro experiment, the interactions between free-living stages of bovine gastrointestinal nematodes and nematophagous fungus Duddingtonia flagrans were evaluated using a faecal culture assay. Faeces were collected from donor calves infected with monocultures of Haemonchus placei, Trichostrongylus axei, Cooperia oncophora and Oesophagostomum radiatum, and the number of parasitic eggs' per gram of faeces (epg) were determined. The assay consisted of 4 faecal worm egg levels: low (40-50 epg), medium (200-280 epg), high (600-680 epg) and very high (1 288-4 800) and 4 fungal concentrations: 0 (controls),1 000, 5 000 and 25 000 chlamydospores/g of faeces. The number of infective third stage larvae which developed in faecal cultures was determined after incubating cultures for 2 weeks in a climatic chamber at 25Â°C and 95% relative humidity. The nematode-trapping capability of D.flagrans was found dependent on the fungal concentration and number of eggs in the faecal cultures. Thus, per cent reductions increased with corresponding increase in fungal concentration and epg levels in all the 4 species of parasitic nematodes. The average trapping efficacy of D. flagrans at the medium epg level exceeded 75% for H. placei, T. axei and C. oncophora compared to 53% for O. radiatum at the 1 000 and 5 000 fungal spore concentrations.